Teacher Performance in Carrying out Cognitive Assessments in Mathematics Learning at State Junior High Schools in the District of Makassar City - Latri Aras; Ahmad Zaki; Rahmawati Patta; Muhammad Idris Jafar (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
This research uses a qualitative approach with the aim of knowing the teacher’s performance in conducting assessments in accordance with learning mathematics to achieve certain competencies in public junior high schools in the Makassar district. Data collection technique using documentation technique, observation technique, and interview technique. The research subjects were 3 mathematics teachers at Rappocini Middle School, Makassar District. The results of the study show that the teacher’s performance in planing cognitive assessments in mathematics at state Junior High School in the makassar city district is able to develop assessments tools that are in accordance with learning objective to achieve certain comptencies as written in the lesson plans. Meanwhile, teacher performance in carrying out cognitve assessments in the subject of mathematics in public middle schools in the district of Makassar city, namely carrying out assessments with various assessmnets technique and announcing the results and their implications for students, regarding the level of understanding of the learning material that has been and will be studied. Teacher performance in analyzing appropriate cognitive assessments by learning mathematics to achieve certain competencies in state Junior High School throughout the District of Makassar City, namely partly analyzing the results of the assessments to identify diffuclt basic indicators/competencies so that the strengths and weaknesses of each studnets are known for remedial and enrcihment purpose. The teacher’s performance in reflecting on the results of cognitive assessments in accordance with learning mathematics achive certain competencies in public middle schools in the district of Makassar City, namely that they have not maximaized/utilized input from students so that they do not reflect enough to imprive learning.